Percent utilization of VO2max at 5-km competition velocity does not determine time performance at 5 km among elite distance runners - Stoa, E. M.; Storen, O.; Enoksen, E.; Ingjer, F. (The Journal of Strength and Conditioning Research, 2010)
The present study investigated to what extent maximum oxygen uptake VO2max) and fractional utilization (%VO2max) in 5-km competition speed correlate with 5-km performance times among elite long distance runners. Eight elite long distance runners with 5-km performance times of 15.10 minutes ( ± 32 seconds) were tested for VO2max during an incremental protocol and for %VO2max during an 8-minute treadmill test at the velocity representing their 5-km seasonal best performance time. There was no correlation between fractional utilization and 5-km performance. The study showed no significant difference between VO2max obtained during an incremental VO2max test and %VO2max when running for 8 minutes at the runner's individual 5-km competition speed. The 5-km time was related to the runner's VO2max even in a homogenous high-level performance group. In conclusion, the present study found no relationship between fractional utilization and 5-km performance time. Training aiming to increase %VO2max may thus be of little or no importance in performance enhancement for competitions lasting up to approximately 20 minutes.